Ki, mikor és kivel házasodik? A házasság helye az egyéni életútban és a történeti időben: (Elméletek és megközelítések) - Bukodi, Erzsébet (Szociológiai Szemle, 2024)
Marriage between members of different social groups has long been viewed as a crucial indicator of the strength of these groups boundaries.This study considers marriage choice as a multidimensional phenomenon and investigates its ascriptive and achievement components. Ascriptive marriage homogamy/heterogamy is interpreted as the similarities/differences in partners’ social origin; the achieved characteristics of marital choices are interpreted as the similarities/differences in spouses’ education and occupation position. The aim of the study is to outline the theoretical background o f the marriage propensity as well as the partner selection process; and - building on the arguments of different economic and sociological theories - to answer the question whether there has been a transition from ascription to achievement in marriage selection processes in Hungary. Mate selection is commonly viewed as to be determined by the individuals’ preferences for similarity in social traits as well as the constraints of marriage market people should face in realizing these preferences. As for the preferences, this study applies two competing approaches - the so-called ‘reward redistribution’ and ‘reward accumulation’ hypotheses. As for the marriage market composition, the study poses the so-called ‘two-sex problem’ which means that males’ and females’ age-specific marriage rates largely depend on the age-sex composition o f the population.